Perlindungan Hukum terhadap Data Pribadi Konsumen dalam Fitur PayLater pada Platform E-Commerce - Angraini, Oktavia Salsabila; Sulistyaningrum, Helena Primadianti (Consensus : Jurnal Ilmu Hukum, 2026)
The advances in digital technology have driven increased use of the PayLater feature on e-commerce platforms because it offers consumers convenience in transactions. However, this convenience also poses risks to personal data protection, particularly regarding the collection, storage, and potential misuse of data by service providers. This study aims to examine the legal protection of consumers’ personal data in the use of the PayLater feature and to assess the effectiveness of existing regulations, particularly Law No. 27 of 2022 on Personal Data Protection. The study employs a normative legal method with a juridical and conceptual approach through a literature review. The findings indicate that while regulations have established obligations for businesses to protect personal data, their implementation still faces shortcomings, particularly regarding transparency, user consent, and oversight. The misuse of personal data also has the potential to lead to various criminal acts, such as theft, online fraud, the creation of fake accounts, money laundering, and illegal transactions. Therefore, it is necessary to strengthen oversight and increase legal awareness among both businesses and consumers so that personal data protection within the digital ecosystem can function optimally.